Linear Relation Between Shifting ITCZ and Dust Hemispheric Asymmetry. Issue 22 (15th November 2020) - Evans, Stuart; Dawson, Eliza; Ginoux, Paul
Abstract: Mineral dust is emitted primarily from arid regions, which may shrink or expand in one or both hemispheres, producing a complex and asymmetric pattern of radiative forcing that varies on interannual to millennial timescales. We assess the impact of hemispheric dust asymmetry on tropical precipitation. Using the Geophysical Fluid Dynamics Laboratory (GFDL) coupled climate model CM3 to simulate dust emission, we vary source strength in each hemisphere individually. Hemispherically asymmetric dust emission produces asymmetric dust load and radiative forcing. We find that the Intertropical Convergence Zone (ITCZ) shifts away from the hemisphere with enhanced dust load in response to the forcing asymmetry. We find significant linear relationships between the hemispheric imbalance and the latitude of tropical precipitation globally, in the Pacific, and especially in the Atlantic basin. This relationship offers a first‐order estimation of dust effects on the hydrological cycle when investigating records of paleodust and for accurately predicting dust effects and feedbacks on future climate. Plain Language Summary: Dust aerosols in the climate system come from desert regions that are unevenly distributed across the globe. Currently, this unevenness produces much more dust in the Northern Hemisphere than in the Southern, but in previous climates, the degree of unevenness has varied. The presence of dust affects atmospheric energy balance by reflecting sunlight and absorbing infrared radiation. One consequence of an atmospheric energy imbalance is that the band of intense tropical rainfall near the equator shifts northward or southward. Using a global climate model, we increased and decreased the amount of dust in each hemisphere independently, creating a range of uneven dustiness and energy imbalance, and studied the tropical rainfall response. We found that tropical rainfall shifts away from the dustier hemisphere in a predictable way over both the Atlantic and Pacific oceans. The shift is especially strong over the Atlantic because it is downwind of the Sahara desert, the largest source of dust. Comparing our findings to records from the last ice age shows that dust accounts for roughly 15% of the shift of rainfall over the Atlantic since then. This dust‐rainfall relationship may also help predict changes to the location of tropical rainfall in the future. Key Points: Hemispherically asymmetric dust emission produces asymmetric radiative forcing that shifts tropical precipitation Increasing dust forcing in the Northern Hemisphere shifts the ITCZ linearly southward in the Atlantic, Pacific, and globally Millenial‐scale dust variability from ocean sediment cores imply dust responsible for 15% of shift in Atlantic ITCZ since the LGM